Production Performance of Two-way and Three-way Crosses in white Leghorns - Reghunathan Nair G (Department of Poultry Science, College of Veterinary and Animal Science, 1977)
The analysis of the performance record of the Two-way and Three-way strain crosses maintained at the Central Poultry Breeding Farm, Hessarghatta, Banglore is reported in this thesis. The strain cross combination studied were MT, TM, MV, VM, VNT, VTM, TMV, and TVM. In order to evaluate the comparative efficiency of these two strain cross procedures egg production, egg weight, body weight, food efficiency and livability were used as the parameters.